A 0.7 V R‐2R SAR ladder‐based temperature sensor with less supply sensitivity. Issue 14 (2nd June 2022) - Xie, Shuang; Yu, Ting; Wang, Yong
Abstract: A 0.7 V, R‐2R SAR ladder‐based temperature sensor with less supply sensitivity is presented, intended for Very Large‐Scale Integration thermal management. Its silicided and non‐silicided resistors in the R‐2R ladders serve as both thermal sensing and quantization elements. The only active component it requires is the comparator, which is compatible with low power supply voltage. The post‐layout simulation results show it has an inaccuracy of 0.5°C between –40°C and 125°C for TT, FF and SS corners.